TRANSACTION COSTS IN MARKETING BUFFALO IN NORTH TORAJA, SOUTH SULAWESI - Sirajuddin, Sitti Nurani; Kasim, Kasmiyati; Rombe, Martha B.; Palmarudi, - (Proceeding Buffalo International Conference, 2013)
The research was aimed to know transaction costs in marketing buffalo at Bolu animal market in North Toraja district. This research was conducted for 4 months started from June 2012 until September 2012. Populations were all buffalo vendors at Bolu animal market in North Toraja district. Samples were buffalo vendors from different regency in North Toraja district Selatan Province. The result showed that transaction costs in marketing buffalo consisted of: transportation cost, administration cost, negotiation cost and retribution cost.